Programme preventing vision loss due to diabetes - Bandurska-Stankiewicz, Elżbieta; Wiatr, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Diabetic visual complications prevention relies, on the one hand, on an intensive metabolic control of diabetes and elimination of coexisting risk factors for development of diabetic retinopathy and, on the other hand on carrying out a programme for early detection and treatment of diabetic retinopathy. Proper treatment of diabetes, expressed by good glycaemia control, proper arterial pressure parameters and lipid concentration in blood reduce the risk of heavy complications and extends life span and improves its quality. An ideal model of screening studies towards diabetic retinopathy is based on an annual examination of vision acuity and eye fundus in all diabetic patients, by an experienced ophthalmologist using precise methods for imaging eye fundus. Examination of the eye fundus completed with fluorescein angiography make a golden standard in retinopathy diagnosis and classification. The incidence of vision loss due to diabetes is significantly lower in the countries which introduced programs preventing retinopathy than in those which do not have them.